Unique Fixed Point Theorem for Weakly C-Contractive Mappings - Choudhury, Binayak S (Kathmandu University Journal of Science Engineering and Technology, 2009)
In this work we introduce the class of weakly c-contractive mappings. We establish that these mappings necessarily have unique fixed points in complete metric spaces. We support our result by an example. Our result also generalises an existing result in metric spaces.